Effects of dietary polyunsaturation level and genistein supplementation on performance and meat quality in quails reared under heat stress - Sahin, N.; Orhan, C. (Elsevier Science Inc, 2010)
[Abstract Not Available]
Keywords: PUFA; genistein; quail